2017
DOI: 10.1101/171827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ketumutant mice uncover an essential meiotic function for the ancient RNA helicase YTHDC2

Abstract: Mechanisms regulating mammalian meiotic progression are poorly understood. Here we identify mouse YTHDC2 as a critical component. A screen yielded a sterile mutant, "ketu", caused by a Ythdc2 missense mutation. Mutant germ cells enter meiosis but proceed prematurely to aberrant metaphase and apoptosis, and display defects in transitioning from spermatogonial to meiotic gene expression programs. ketu phenocopies mutants lacking MEIOC, a YTHDC2 partner. Consistent with roles in post-transcriptional regulation, Y… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 122 publications
2
55
0
Order By: Relevance
“…Consistently with its high expression in mammalian germlines [55][56][57], YTHDC2 is required for proper male and female fertility. Ythdc2-deficient mice are viable but infertile with males and females having smaller testes and ovaries respectively.…”
Section: Gametogenesismentioning
confidence: 70%
“…Consistently with its high expression in mammalian germlines [55][56][57], YTHDC2 is required for proper male and female fertility. Ythdc2-deficient mice are viable but infertile with males and females having smaller testes and ovaries respectively.…”
Section: Gametogenesismentioning
confidence: 70%
“…Many studies have indicated YTHDC2 to be crucial for fertility in both male and female mice, with particular importance in spermatogenesis [21][22][23][24] . Other studies have indicated that YTHDC2 may be related to autism spectrum disorder [25] , hepatitis C [21] , pancreatic adenocarcinoma [26] , and CRC [27] . The present research demonstrates that the expression of YTHDC2 is negatively correlated with overall survival and tumor stage in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…YTHDC2 is an RNA-induced ATPase with a 3′ -to-5′ RNA helicase activity [97]. Germ cells down-regulated YTHDC2 enter meiosis but process prematurely to abnormal metaphase and apoptosis [98,99].…”
Section: Ythdc2mentioning
confidence: 99%